Criminology post-Maastricht - Taylor, Ian R. (Crime, law and social change, 1998)
My objectives in this paper are to try and identify the range of challenges that now confront critical criminologists who work in, and are attentive to, the "new Europe" whose construction was so clearly signalled by the Maastricht Treaty (the Treaty on European Union) of 1993. I want to concentrate here on two issues - firstly, the challenge of situating the work of criminology in relation to the process of political union (and enlargement) of the European Union, and, secondly, the articulation of an agenda of work for critical criminology, that derives, from an understanding of this broader context.